Aesthetic and functional rehabilitation of missing teeth in growing patients with mini-implants: a contemporary approach - Sarkar, Nilanjana; Goel, Sumit; Reddy, Sumitra; Belludi, Anup; B.C., Karunakara (International Journal of Research in Medical Sciences, 2021)
Growing patients with missing teeth in aesthetically prominent areas pose a challenge in restoration of the same. Fracture of anterior teeth in these age groups is very common and often requires removal of the affected tooth. After the decision to maintain the space in the dental arch is made, some other factors have to be borne in mind before restoration of the space. Continuing growth of the alveolar bones, questionable cooperation of the patient and aesthetics are deciding factors that may limit the treatment options. The effective use of mini-implants for space preservation, alveolar bone width maintenance and aesthetics represents an elective way of successfully treating such cases. The aim of this article is to describe as well as highlight the advantages and ease of the procedure with the help of two clinical cases.